BPEL PM and OSB operational management with Oracle Enterprise Manager 10g Grid Control : manage the operational tasks for multiple BPEL and OSB environments centrally /: manage the operational tasks for multiple BPEL and OSB environments centrally. (©2010) - Unknown
No abstract available